Pengaruh pemahaman dasar akuntansi dan penerapan akuntansi terhadap pencatatan keuangan UMKM di Pamekasan - Sinta Nor Halisah; Sri Handayani (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving national economic growth, particularly through their contribution to job creation and Gross Domestic Product (GDP). However, in practice, many MSME operators still face problems with financial record-keeping due to insufficent basic accounting understanding and suboptimal accounting practices. This study aims to analyse the influence of basic accounting understanding and the application of accounting on the financial record-keeping of MSMEs in Pamekasan. This study employs a quantitative approach using a survey method involving 50 food and beverage MSME operators operating in the Pamekasan food colony. The results indicate that basic accounting understanding and the application of accounting have a positive influence on the financial record-keeping of MSMEs. Consequently, it can be concluded that improving the quality of financial record-keeping in MSMEs requires adequate accounting knowledge and consistent application of accounting practices.